BURDEN OF CYTOPAENIAS AMONG HIV POSITIVE PREGNANT WOMEN AT THE UNIVERSITY COLLEGE HOSPITAL, IBADAN - Adesina, O.A. (Ann Ib Postgrad Med, 2018)
INTRODUCTION: Few studies have examined cytopaenia among HIV positive pregnant women. OBJECTIVES: To assess burden of cytopaenia among HIV positive pregnant women. METHODOLOGY: This cross-sectional study of women on HAART ≤6months, defined anemia as hematocrit <33%, leucopenia as total white blood cell count <3,000 cells/mm(3) and thrombocytopenia as absolute platelet count <100,000 cells/mm(3). Univariate and bivariate analyses were performed. RESULTS: Over 8 years, of 1,197 women, the mean age was 29.02(±5.4) years and mean gestational age 25.9(±8.1) weeks. Prevalence of anaemia was 76.8%, leucopaenia 6.9% and thrombocytopenia 4.7%. The mean haematocrit was 28.5%(±4.5); median white blood count 5,500/mm(3) ; median platelet count 200,000/mm(3) and median CD4 323 cells/mm(3). Mean haematocrit was highest (29.7%±5.3) in women in the first trimester but lowest (28.4% ±4.6) in women in second trimester (p=0.04). Compared with earlier trimesters, women in the third trimester had higher median white blood count (5,600 cells/mm(3)), higher neutrophil (61.0% ±11.2) but lower lymphocytes (28.3%± 9.2) (p=0.18; 0.00, 0.00). Median absolute platelet count was highest (206,000 cells/mm(3)) in the first trimester but lowest (195,000 cells/mm(3)) in third trimester (0.04). Women with lower CD4 had higher prevalence of cytopaenias. CONCLUSION: Cytopaenias are not uncommon in this population especially with lower CD4.